PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERORIENTASI GEMINI AI TERHADAP MOTIVASI BELAJAR SISWA KELAS V PADA PEMBELAJARAN IPAS DI SD NEGERI 2 NUSASARI KABUPATEN JEMBRANA - Ayunita Putri, Ni Kadek Cahya; Pusparini, Luh Dewi; Made Gautama Jayadiningrat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students' learning motivation in Integrated Science and Social Studies (IPAS), which is caused by teacher-centered learning practices and the limited use of technology in the learning process. One alternative approach to address this issue is the implementation of the Project Based Learning (PjBL) model integrated with Gemini AI as a learning support tool. This study aimed to determine the effect of the Project Based Learning model oriented toward Gemini AI on the learning motivation of fifth-grade students in IPAS at SD Negeri 2 Nusasari, Jembrana Regency. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The population as well as the sample consisted of all fifth-grade students of SD Negeri 2 Nusasari. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability. The data were analyzed using descriptive statistics, the normality test, and hypothesis testing through the Paired Sample t-Test. The results showed that students' learning motivation increased after the implementation of the Project Based Learning model oriented toward Gemini AI. The Paired Sample t-Test produced a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Therefore, it can be concluded that the Project Based Learning model oriented toward Gemini AI has a significant effect on the learning motivation of fifth-grade students in IPAS at SD Negeri 2 Nusasari, Jembrana Regency. The implementation of this learning model creates a more active, interactive, collaborative, and meaningful learning environment, thereby enhancing students' engagement and learning motivation.